2015
DOI: 10.1007/s11005-015-0769-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conservation, Counting Statistics, and Return to Equilibrium

Abstract: Abstract. We study a microscopic Hamiltonian model describing an N -level quantum system S coupled to an infinitely extended thermal reservoir R. Initially, the system S is in an arbitrary state while the reservoir is in thermal equilibrium at inverse temperature β. Assuming that the coupled system S + R is mixing with respect to the joint thermal equilibrium state, we study the Full Counting Statistics (FCS) of the energy transfers S → R and R → S in the process of return to equilibrium. The first FCS describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Return to equilibrium was also shown for finite quantum systems coupled to infinite reservoirs after a coupling has been turned on [18,19], and a rough argument for stability of thermal states was given recently in terms of energy probability distributions in [20]. Here, we prove that a system in a thermal state, after being locally disturbed, re-equilibrates to a thermal state provided correlations decay sufficiently quickly.…”
Section: Introductionsupporting
confidence: 57%
“…Return to equilibrium was also shown for finite quantum systems coupled to infinite reservoirs after a coupling has been turned on [18,19], and a rough argument for stability of thermal states was given recently in terms of energy probability distributions in [20]. Here, we prove that a system in a thermal state, after being locally disturbed, re-equilibrates to a thermal state provided correlations decay sufficiently quickly.…”
Section: Introductionsupporting
confidence: 57%
“…As conveyed e.g. in [JOPP11], [JPPP15] and [BJP + 15], mild assumptions ensure that the corresponding sequence of probability measures converges weakly to the measure P t of Definition 3.1 on the limiting infinitely extended system. In Appendix B, we provide proofs of this weak convergence for the models studied in Section 4.…”
Section: Setupmentioning
confidence: 99%
“…Note that, while important for the control of the tails at finite λ, the UV regularisation assumptions become irrelevant in the limit t → ∞ and then λ → 0, if one assumes return to equilibrium. Indeed, adapting [JPPP15], it can be shown that in this limit P t converges weakly to a Dirac measure in 0.…”
Section: Introductionmentioning
confidence: 96%
“…In the case where A and B are thermal reservoirs, the FCS of the total energy current was previously studied theoretically in [21]. The works [22,23] concern the FCS of energy transfer in the thermalization process of a finite level quantum system in contact with a thermal bath, a problem which is radically different from the one considered here. We also emphasize that here we are only interested in the FCS of the total energy, and not in the FCS of the individual energy variations ∆E A/B .…”
mentioning
confidence: 99%